Modifikasi Formula Khusus untuk Pasien dengan Diet TKTP Berbahan Dasar Tepung Tempe, Tepung Jagung, dan Tepung Ikan Lele: Formula Modifications for Patients with TKTP Diet Ingredients Based on Tempe Flour, Corn Flour (Zea Mays) and Catfish Flour - Indah Puspita Sari; Imelda Telisa; Terati (UNIVERSITAS NGUDI WALUYO, 2023)
Enteral formula is food in liquid form which is given to patients through mouth or tube (sonde) as long as the digestive tract is still functioning. One of the enteral formulas that is widely used in hospitals is the enteral formula for patients on the TKTP diet who require higher energy and protein than normal requirements. One of the efforts that can be made is through an enteral formula product innovation approach for the TKTP diet based on local food of high nutritional value.To find out the best formulation of a formula esspecially for the TKTP diet made from tempe flour, corn flour, and catfish flour, macronutrient content, viscosity, and acceptability. This research is an experimental study using a non-factorial Completely Randomized Design (CRD) with 3 formulations. The subjects of the organoleptic test were 25 panelists. Based on the results of organoleptic tests (color, aroma, taste, and texture) it showed that the most favorable acceptability of the formula was F3 with 452.33 kcal energy, 20.80% protein, 17.29% fat, 53.38% carbohydrates, in 100 grams and a viscosity yield of 7.8 mpa.s. Based on the research results, this formulation made from tempe flour, corn flour and catfish flour can be used as an alternative enteral formula for patients on the TKTP diet. ABSTRAK Formula enteral merupakan makanan dalam bentuk cair yang diberikan kepada pasien melalui oral atau pipa (sonde) selama saluran cerna masih berfungsi. Salah satu upaya yang dapat dilakukan adalah melalui pendekatan inovasi produk formula enteral untuk diet TKTP berbahan dasar pangan lokal bernilai gizi tinggi. Untuk mengetahui formulasi terbaik formula khusus untuk diet TKTP berbahan dasar tepung tempe, tepung jagung, dan tepung ikan lele, kandungan gizi makro, viskositas, dan daya terimanya. Penelitian ini merupakan penelitian eksperimental dengan menggunakan Rancangan Acak Lengkap (RAL) non faktorial dengan 3 formulasi. Subjek penelitian uji organoleptik sebanyak 25 panelis. Berdasarkan hasil penelitian uji organoleptik (warna, aroma, rasa, dan tekstur) menunjukkan bahwa daya terima formula yang paling disukai adalah F3 dengan energi 452,33 kkal, protein 20,80%, lemak 17,29%, karbohidrat 53,38%, dalam 100 gram dan hasil viskositas 7,8 mpa.s. Berdasarkan hasil penelitian formula khusus berbahan dasar tepung tempe, tepung jagung dan tepung ikan lele ini bisa digunakan sebagai formula enteral alternatif untuk pasien dengan diet TKTP.